Generosity and social distance in dictator game field experiments with and without a face - Sosina Bezu; Stein T. Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2013)
Field experiments combining dictator games with stated preference questions are used to elicit within subject and between subject sharing behavior with known family members and anonymous villager. A simple theoretical model incorporating social preferences, social distance and inter-dependent preferences is developed. The results show that generosity in form of probability of giving and amounts given are much lower towards anonymous villagers than to known family members. The probability of giving to the spouse is positively correlated with probability of giving to anonymous villager. Husbands and wives receiving positive amounts from their spouses (without knowing), were also more likely to give positive amounts to their spouses than those that received nothing from their spouses. Receiving positive amounts from spouse was uncorrelated with giving behavior towards anonymous villager. How sharing behavior is correlated with marriage type (parental arrangement, parental and bride agreement, love marriage, and kidnapping marriage), and other socioeconomic characteristics was assessed separately for husbands and wives to explore the sensitivity of responses to such socio-economic characteristics.
Keywords: C93; D03; O12; 330; Generosity; social distance; within-family generosity